ABOUT THE PROBLEMS OF RECOGNITION AND IMPLEMENTATION OF INNOVATIVE TECHNOLOGIES AND RELATIONS OF SCIENTISTS WITH STATE INSTITUTIONS OF POWER - Савенко, Володимир; Нестеренко, Ірина; Клюєва, Вікторія; Полосенко, Олександр; Куліков, Петро (SWorldJournal, 2024)
The history of the relationship between individual scientists, scientific organizations, and official state scientific institutions has always been complex and often dramatic. This remains true today. The paper recalls the names of great scientists throug